Healthful and unhealthful provegetarian food patterns and micronutrient intake adequacy in the SUN cohort - Daniela Asfura-Carrasco; Susana Santiago; Itziar Zazpe; Clara Gómez-Donoso; Maira Bes-Rastrollo; Miguel Ángel Martínez-González (Cambridge University Press, 2023)
Abstract Objective: To investigate the association between different versions of a provegetarian food pattern (FP) and micronutrient inadequacy. Design: Cross-sectional analysis. Dietary intake was assessed at baseline through a validated 136-item FFQ. Participants were classified according to groups of different versions of a provegetarian FP: overall, healthful and unhealthful. The prevalence of inadequate intake of vitamins B1, B2, B3, B6, B12, C, A, D, E, folic acid, Zn, I, Se, Fe, Ca, K, P, Mg and Cr was evaluated using the estimated average requirement (EAR) cut-point method and the probabilistic approach. Logistic regression analyses were conducted to estimate the probability of failing to meet EAR for either ≥ 3 or ≥ 6 micronutrients. Setting: Seguimiento Universidad de Navarra (SUN) cohort. Participants: 17 825 Spanish adults. Results: Overall, subjects in the highest group of the unhealthful provegetarian FP had the highest prevalence of inadequate dietary intake for every vitamin and mineral, compared to those in the lowest group. The adjusted OR of failing to meet ≥ 3 EAR (highest v. lowest group) was 0·65 (0·54, 0·69) for the overall, 0·27 (0·24, 0·31) for the healthful and 9·04 (7·57, 10·4) for the unhealthful provegetarian FP. Conclusion: A higher adherence to an overall and healthful provegetarian FP was inversely associated with the risk of failing to meet EAR values, whereas the unhealthful version was directly associated with micronutrient inadequacy. Provegetarian FP should be well planned, prioritising nutrient-dense plant foods and minimising ultra-processed and unhealthy ones.